Research on the influence of polar solvents on CsPbBr3 perovskite QDs. Issue 44 (10th August 2021) - Sun, Yifang; Zhang, Huidan; Zhu, Kai; Ye, Weiguang; She, Lushuang; Gao, Ximing; Ji, Wenyu; Zeng, Qinghui
Abstract : All-inorganic CsPbX3 (X = Cl, Br, I) perovskite quantum dots (QDs) have become a kind of optoelectronic material with huge application prospects due to their excellent physical and optical properties. Abstract : All-inorganic CsPbX3 (X = Cl, Br, I) perovskite quantum dots (QDs) have become a kind of optoelectronic material with huge application prospects due to their excellent physical and optical properties. However, their poor structural stability to the external environment, especially polar solvents, seriously hinder further development in practical applications. Considering whether polar solvents have the same effects on perovskites QDs, few studies have been investigated in this area presently. In order to find out the effect of different polar solvents on all-inorganic perovskite QDs, in this work, we select 12 kinds of polar solvents of methanol, ethanol, isopropanol, 1-butanol, 1-pentanol, 1-octanol, N, N -dimethylformamide (DMF), tetramethylethylenediamine (TMEDA), ethyl acetate, n -butyl acetate, dibutyl phthalate and acetone for a specific analysis. The characterization of their morphology, optical and physicochemical properties shows that different polar solvents have different effects on all-inorganic perovskite QDs, but their effects are regular. Polar solvents act on the ligands preferentially, and the effects can be divided into: reducing the concentration of ligands; substituting ligands partially; completely destroying the surface ligands; polar solvents with the same functional group, as the polarity of the solvent increases, the impact on all-inorganic perovskite QDs is greater. We believe that this discovery has important implications for improving the stability of all-inorganic perovskite QDs.